Respostas
respondido por:
1
Olá !
Resolução :
4 + 3X = -X² + 2
3X + X² = 2 - 4
3X + X² = -2
3X + X² + 2 = 0
X² + 3X + 2 = 0
A = 1 ; B = 3 ; C = 2
∆ = b² - 4 • a • c
∆ = 3² - 4 • 1 • 2
∆ = 9 - 8
∆ = 1
X = -b ± √∆ / 2 • a
X = -3 ± √1 / 2 • 1
X = -3 ± 1 / 2
X' = -3 + 1 / 2
X' = -2 / 2
X' = -1
X'' = -3 - 1 / 2
X'' = -4 / 2
X'' = -2
Resposta :
S = { -1 , -2 }
Resolução :
4 + 3X = -X² + 2
3X + X² = 2 - 4
3X + X² = -2
3X + X² + 2 = 0
X² + 3X + 2 = 0
A = 1 ; B = 3 ; C = 2
∆ = b² - 4 • a • c
∆ = 3² - 4 • 1 • 2
∆ = 9 - 8
∆ = 1
X = -b ± √∆ / 2 • a
X = -3 ± √1 / 2 • 1
X = -3 ± 1 / 2
X' = -3 + 1 / 2
X' = -2 / 2
X' = -1
X'' = -3 - 1 / 2
X'' = -4 / 2
X'' = -2
Resposta :
S = { -1 , -2 }
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás